A Study of Roughness Improvement of Al2O3 Substrates Using Sol-Gel Method. (2016) - Liu, Tung-Yueh; Teoh, Lay-Gaik; Huang, Chao-Kai; Lee, Ying-Chieh
Abstract: In this study, pure SiO2 and SiO2 -CaO-ZnO sol-gel were coated on alumina substrates, respectively. The effects of coating conditions and sintering temperatures on the phase structures, microstructures, surface roughness and mechanical properties of coatings were studied. For SiO2 coating layer, the roughness of Al2 O3 substrates improved significantly at 1300 °C, and the average roughness was approximately 15.4 nm based on the thickness of coating layer which was about 1.69 μm. In conclusion, the study derived that for SiO2 -CaO-ZnO coatings, the roughness of Al2 O3 substrates improved at 1200 °C, and the average roughness was < 20 nm based on the thickness of coatings (about 1.0 μm). However, the adhesive force of coatings was achieved at about 21.4 MPa.